The Effect of Perceived Social Media Marketing Activities on Brand Loyalty in the Fast Fashion Industry the Mediation Effect of Brand and Value Consciousness - Jordy Soesanto; Verina Halim (Budapest International Research and Critics University, 2022)
Social media has become an important platform for online marketing events. This media is used to establish a better relationship with customers. While many previous studies have examined social media, only a few have explained the effects of social media marketing activity. This study aimed to determine the impact of perceived social media marketing activity on brand loyalty, value consciousness, and brand consciousness. To empirically test the effects of social media marketing activities, this study conducted an online survey of social media users for data analysis then, to estimate the variables’ relationships in the model, structural equation modeling with AMOS 26 is used. The results showed that perceived social media marketing activities had a negative effect on brand loyalty.